Clinical presentation, treatment and outcome in dogs with pemphigus foliaceus with and without vasculopathic lesions: an evaluation of 41 cases. Issue 5 (29th June 2021) - Zhou, Zijin; Corner, Sarah; Petersen, Annette; Rosser, Edmund; Noland, Erica L
Abstract : Background: Concurrent vasculopathic lesions in dogs with pemphigus foliaceus (PF) have been observed anecdotally yet not reported in the literature. Any association with prognosis is unclear. Hypothesis/Objectives: To compare clinical features and outcome of PF in dogs with and without vasculopathic lesions. Animals: Archived, formalin‐fixed, paraffin‐embedded biopsy samples of 41 dogs with PF. Methods and materials: Archived, formalin‐fixed, paraffin‐embedded biopsy samples with a histological diagnosis of PF were selected and re‐evaluated independently. Dogs were assigned to groups following histological evaluation: Group 1 (no vasculopathic lesions) and Group 2 (vasculopathic lesions present). Group 2 was subdivided into Group 2a (vasculopathic lesions without vasculitis – i.e. vasculopathy) and Group 2b (overt vasculitis). Medical records from identified cases were reviewed retrospectively for data on clinical presentation, treatment and outcome. Results: Time to remission was longer in Group 2b (93.8 days) compared to Group 1 (41.8 days) ( P  = 0.047). Dogs in groups 2a and 2b were more likely to have systemic signs of illness at presentation ( P  = 0.028 and P  = 0.032, respectively) compared to Group 1. Dogs in Group 2b were more likely to have adverse effects associated with treatment than dogs in Group 1 ( P  = 0.004). There were no significant differences in lesion type, distribution, rates of remission, recurrence or corticosteroid dosage between groups. Conclusions and clinical importance: Dogs with PF and concurrent vasculitis took longer to achieve remission and were more likely to have systemic signs of illness or adverse effects associated with treatment than dogs with PF without concurrent vasculopathic lesions. Abstract : Background – Concurrent vasculopathic lesions in dogs with pemphigus foliaceus (PF) have been observed anecdotally yet not reported in the literature. Any association with prognosis is unclear. Hypothesis/Objectives – To compare clinical features and outcome of PF in dogs with and without vasculopathic lesions. Conclusions and clinical importance – Dogs with PF and concurrent vasculitis took longer to achieve remission and were more likely to have systemic signs of illness or adverse effects associated with treatment than dogs with PF without concurrent vasculopathic lesions. RÉSUMÉ: Contexte: Les lésions vasculopathiques concomitantes des pemphigus foliacé (PF) chez le chien ont été observées anecdotiquement dans la littérature. Une association avec un pronostic n'est pas claire. Hypothèses/Objectifs: Comparer les données cliniques et l'évolution des PF chez le chien avec et sans lésions vasculopathiques. Sujets: Des biopsies dans la paraffine, fixées dans le formol paraffine, archivées de 41 chiens avec PF. Méthodes: Les biopsies avec diagnostic de PF ont été sélectionnées et réévaluées de façon indépendante. Les chiens ont été assignés aux groupes selon l'évaluation histologique: Groupe 1 (pas de vasculopathie) et Groupe 2 (présence de lésion de vasculopathie). Le Groupe 2 a été divisé en Groupe 2a (lésions vasculopathiques sans vascularite ‐ i.e. vasculopathie) et Groupe 2b (nette vascularite). Les données médicales des cas identifiés ont été revues rétrospectivement pour les données de présentation clinique, le traitement et le suivi. Résultats: Le temps de rémission était plus long dans le Groupe 2b (93.8 jours) comparé au Groupe 1 (41.8 jours) ( P = 0.047). Les chiens des groupes 2a et 2b développaient davantage de signes systémiques ( P = 0.028 et P = 0.032, respectivement) comparé au Groupe 1. Les chiens du Groupe 2b présentaient davantage d'effets secondaires associés au traitement que les chiens du Groupe 1 ( P = 0.004). Il n'y avait pas de différence significative dans le type de lésion, la distribution, les taux de rémission, les récidives ou les dosages de corticoïdes entre les groupes. Conclusions et importance clinique: Les chiens avec PF et vascularite concomitante prennent plus de temps pour atteindre une rémission et étaient plus prompts à développer des signes systémiques ou des effets indésirables liés aux traitements que les chiens avec PF sans lésion de vasculopathie associée. RESUMEN: Introducción: de forma anecdótica, se han observado lesiones vasculopáticas concurrentes en perros con pénfigo foliáceo (PF), pero no se han descrito en la literatura. No está clara ninguna asociación con el pronóstico. Hipótesis/Objetivos: Comparar las características clínicas y la progresión de PF en perros con y sin lesiones vasculopáticas. Animales: muestras de biopsia archivadas, fijadas en formalina e incluidas en parafina de 41 perros con PF. Métodos: se seleccionaron y reevaluaron de forma independiente muestras de biopsia archivadas, fijadas en formalina e incluidas en parafina con un diagnóstico histológico de PF. Los perros se asignaron a los grupos siguiendo la evaluación histológica: Grupo 1 (sin lesiones vasculopáticas) y Grupo 2 (lesiones vasculopáticas presentes). El grupo 2 se subdividió en el grupo 2a (lesiones vasculopáticas sin vasculitis, es decir, vasculopatía) y el grupo 2b (vasculitis manifiesta). Los historiales clínicos de los casos identificados se revisaron retrospectivamente para obtener datos sobre la presentación clínica, el tratamiento y el resultado. Resultados: el tiempo para obtener remisión fue mayor en el Grupo 2b (93, 8 días) en comparación con el Grupo 1 (41, 8 días) ( P = 0, 047). Los perros de los grupos 2a y 2b tenían más probabilidades de presentar signos sistémicos de enfermedad en el momento de la presentación ( P = 0, 028 y P = 0, 032, respectivamente) en comparación con el Grupo 1. Los perros del Grupo 2b tenían más probabilidades de tener efectos adversos asociados con el tratamiento que los perros del Grupo 1 ( P = 0, 004). No hubo diferencias significativas en el tipo de lesión, distribución, tasas de remisión, recurrencia o dosis de corticosteroides entre los grupos. Conclusiones e importancia clínica: los perros con PF y vasculitis concurrente tardaron más en lograr la remisión y tenían más probabilidades de presentar signos sistémicos de enfermedad o efectos adversos asociados con el tratamiento que los perros con PF sin lesiones vasculopáticas concurrentes. Zusammenfassung: Hintergrund: Gleichzeitig auftretende pathologische Gefäßläsionen bei Hunden mit Pemphigus foliaceus (PF) sind anekdotisch beobachtet, aber in der Literatur noch nicht beschrieben worden. Ein Zusammenhang mit der Prognose ist unklar. Hypothese/Ziele: Ein Vergleich der klinischen Merkmale und das Ergebnis von PF bei Hunden mit und ohne pathologischen Gefäßläsionen. Tiere: Archivierte, in Formalin‐fixierte und in Paraffin eingebettete Biopsieproben von 41 Hunden mit PF. Methoden: Archivierte, in Formalin‐fixierte und in Paraffin eingebettete Biopsieproben mit der histopathologischen Diagnose eines PF wurde ausgesucht und unabhängig re‐evaluiert. Die Hunde wurden nach histologischer Evaluierung in Gruppen eingeteilt: Gruppe 1 (keine pathologischen Gefäßveränderungen) und Gruppe 2 (pathologische Gefäßveränderungen). Gruppe 2 wurde unterteilt in Gruppe 2a (pathologischen Gefäßveränderungen ohne Vasculitis – i.e. Vaskulopathie) und Gruppe 2b (deutliche Vaskulitis). Die medizinischen Patientendaten von identifizierten Fällen wurden retrospektiv in Bezug auf klinische Präsentation, Behandlung und Endergebnis durchgesehen. Ergebnisse: Die Zeit bis zur Remission war in Gruppe 2b (93, 8 Tage) im Vergleich zu Gruppe 1 (41, 8 Tage) länger. Bei Hunden in Gruppe 2a und 2b waren systemische Anzeichen von Erkrankung zum Zeitpunkt der Präsentation wahrscheinlicher ( P = 0, 028 bzw P = 0, 032) als in Gruppe 1. Hunde in Gruppe 2b hatten häufiger Nebenwirkungen im Zusammenhang mit der Behandlung als Hunde in Gruppe 1 ( P = 0, 004). Zwischen den Gruppen bestanden keine signifikanten Unterschiede beim Typ der Läsionen, ihrer Verteilung, der Remissionsraten, dem Wiederauftreten oder der verabreichten Cortisondosis. Schlussfolgerungen und klinische Bedeutung: Hunde mit PF und gleichzeitigen pathologischen Gefäßveränderungen benötigten eine längere Zeit, um eine Remission zu erzielen und hatten häufiger systemische Anzeichen von Erkrankung oder Nebenwirkungen im Zusammenhang mit der Behandlung als Hunde mit PF ohne gleichzeitige pathologische Gefäßveränderungen. 要約: 背景: 落葉状天疱瘡 (PF) の犬における血管病変の併発は、逸話的に観察されているが、文献的には報告されていない。また、予後との関連も不明である。 仮説・目的: 本研究の目的は、PF犬において血管病変のある犬とない犬の臨床的特徴および予後を比較することであった。 供試動物: PFを発症した41頭の保存されたホルマリン固定、パラフィン包埋バイオプシーサンプル。 方法: PFの組織学的診断を受けた保存されたホルマリン固定、パラフィン包埋生検サンプルを選択し、独立して再評価した。組織学的評価の後、グループ1 (血管病変なし) およびグループ2 (血管病変あり) に犬を分けた。グループ2は、グループ2a (血管炎を伴わない血管病変、すなわち血管障害) およびグループ2b (顕在化した血管炎) に細分化された。同定された症例の医療記録を回顧的にレビューし、臨床症状、治療、転帰に関するデータを得た。 結果: 寛解までの期間は、グループ1(41.8日) に比べ、グループ2b(93.8日) の方が長かった (P = 0.047) 。グループ2aおよび2bの犬は、グループ1の犬と比較して、来院時に全身性の病気の兆候がある可能性が高かった (それぞれP = 0.028およびP = 0.032) 。 グループ2bの犬は、グループ1の犬と比較して、治療に伴う副作用がある可能性が高かった (P = 0.004) 。病変の種類、分布、寛解率、再発率、副腎皮質ステロイドの投与量にはグループ間で有意な差はなかった。 結論と臨床上の重要性: PFと血管炎を併発している犬は、血管病変を併発していないPFの犬に比べて、寛解に至るまでに時間がかかり、全身性の病気の兆候や治療に伴う副作用が出やすかった。 摘要: 背景: 在落叶型天疱疮(PF)犬中观察到并发血管病变, 但文献中未见报告。与预后的任何相关性尚不清楚。 假设/目的: 比较有和无血管病变的PF患犬的临床特征和结果。 动物: 被存档的41只PF犬的福尔马林固定、石蜡包埋活检样本。 方法: 存档的福尔马林固定、石蜡包埋活检标本, 组织学诊断为PF, 被独立选择并重新评价。根据组织学评价将犬分组: 组1 (无血管病变) 和组2 (存在血管病变) 。第2组又分为第2a组 (无血管炎的血管病变‐即血管病) 和第2b组 (明显血管炎) 。对选出病例的病历记录进行回顾性审查, 以获得关于临床表现、治疗和结果的数据。 结果: 与第1组 (41.8天) 相比, 第2b组 (93.8天) 的至缓解时间更长(P = 0.047)。与第1组相比, 第2a组和第2b组中的犬在就诊时更可能出现全身性疾病体征 (分别为P = 0.028和P = 0.032) 。第2b组中的犬比第1组中的犬更可能出现与治疗相关的不良反应(P = 0.004)。组间病灶类型、分布、缓解率、复发或皮质类固醇剂量差异均无统计学意义。 结论和临床重要性: 与未并发血管病变的PF犬相比, 并发血管炎的PF犬需要更长的时间才能达到缓解, 并且更可能出现与治疗相关的全身性疾病体征或不良反应。 Resumo: Contexto: A presença de lesões causadas por vasculopatia concomitantemente com o pênfigo foliáceo (PF) em cães já foi observada de forma anedótica, mas ainda não relatada na literatura. Não está claro se há associação disto com o prognóstico. Hipótese/Objetivos: Comparar as características clínicas e a evolução do PF em cães com e sem lesões de vasculopatia. Animais: Foram analisadas 41 amostras arquivadas de biópsia cutânea de cães com PF parafinadas e fixadas em formol. Métodos: Amostras de biópsia cutânea parafinadas e fixadas em formol arquivadas com o diagnóstico histológico de PF foram selecionadas e reavaliadas de forma independente. Os cães foram divididos em grupos de acordo com a avaliação histológica: Grupo 1 (sem lesões vasculopáticas) e Grupo 2 (presença de lesões vasculopáticas). O Grupo 2 foi subdividido em Grupo 2ª (lesões vasculopáticas sem vasculite – vasculopatia) e Grupo 2b (vasculite evidente). Os prontuários dos casos identificados foram revisados retrospectivamente e foram registrados os dados de apresentação clínica, tratamento e evolução. Resultados: O tempo até a remissão foi maior no Grupo 2b (93, 8 dias) em comparação com o Grupo 1 (41, 8 dias) (P =0, 047). Os cães dos grupos 2a e 2b foram mais propensos a apresentar sinais sistêmicos ( P =0, 028 e P =0, 032, respectivamente) em comparação com o Grupo 1. Os cães do Grupo 2b foram mais propensos a ter efeitos adversos associados ao tratamento do que os cães do Grupo 1 ( P =0, 004). Não houve diferenças significativas no tipo de lesão, distribuição, frequência de remissão, recorrência ou dosagem de corticosteroide entre os grupos. Conclusões e importância clínica: Cães com PF e vasculite concomitante demoraram mais para atingir a remissão e foram mais propensos a ter sinais sistêmicos ou efeitos adversos associados ao tratamento do que cães com PF sem lesões vasculopáticas concomitantes.